The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1037/a0028876
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious congruency priming from unpracticed words is modulated by prime–target semantic relatedness.

Abstract: Participants performed a 2-choice categorization task on visible word targets that were preceded by novel (unpracticed) prime words. The prime words were presented for 33 ms and followed either immediately (Experiments 1-3) or after a variable delay (Experiments 1 and 4) by a pattern mask. Both subjective and objective measures of prime visibility were used in all experiments. On 80% of the trials the primes and targets belonged to different categories (incongruent trials), whereas in the remaining 20% (congru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 58 publications
3
17
1
Order By: Relevance
“…In support of this argument, some recent studies have consistently demonstrated that stemming from the same semantic category as the target is not sufficient for a masked prime word to elicit reliable congruency priming effects (e.g., Ortells, Marí-Beffa, & Plaza-Ayllón, 2013;Van den Bussche, Smets, Sasanguie, & Reynvoet, 2012). For example, by using a masked congruency priming task Ortells et al (2013) found reliable priming effects from unpracticed prime words, only when they were followed by strongly related, but not by weakly related targets.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In support of this argument, some recent studies have consistently demonstrated that stemming from the same semantic category as the target is not sufficient for a masked prime word to elicit reliable congruency priming effects (e.g., Ortells, Marí-Beffa, & Plaza-Ayllón, 2013;Van den Bussche, Smets, Sasanguie, & Reynvoet, 2012). For example, by using a masked congruency priming task Ortells et al (2013) found reliable priming effects from unpracticed prime words, only when they were followed by strongly related, but not by weakly related targets.…”
Section: Introductionmentioning
confidence: 76%
“…In support of this argument, some recent studies have consistently demonstrated that stemming from the same semantic category as the target is not sufficient for a masked prime word to elicit reliable congruency priming effects (e.g., Ortells, Marí-Beffa, & Plaza-Ayllón, 2013;Van den Bussche, Smets, Sasanguie, & Reynvoet, 2012). For example, by using a masked congruency priming task Ortells et al (2013) found reliable priming effects from unpracticed prime words, only when they were followed by strongly related, but not by weakly related targets. These findings are difficult to explain in terms other than a semantic processing of masked words, as both strongly and weakly related pairs did not differ in terms of either prime-target orthographic overlap, response congruency (e.g., Wentura, 2000), stimulus-response mappings, or action-triggers for semantic categories (Kiesel et al, 2006).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations